The effect of N-3 fatty acid (fish oil) supplementation on plasma low-density lipoprotein composition and metabolism in vervet monkeys (Cercopithecus aethiops) on atherogenic or therapeutic diets - Van Jaarsveld, P. J.(Paul Johannes) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1994.